Kesulitan Membedakan Soal Cerita FPB Dengan KPK pada Siswa Tingkat Sekolah Menengah Pertama - Pasaribu, Anita Sabrina; Panggabean, Ellis M.; Tambunan, Hardi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the difficulties in distinguishing FPB and KPK story questions in junior high school students. This study uses a qualitative descriptive method. Data collection was carried out through observation, interviews, and document analysis. Observations are made during mathematics learning to identify students' problem-solving approaches. The collected data is analyzed using thematic analysis. The results of data analysis show that the presentation of questions in the form of stories is an effort to create a story to apply the concepts being learned according to daily experience. The difficulty of students distinguishing between FPB and KPK stories lies in the question model. The way to distinguish between FPB and KPK story problems is to plant the concept that FPB is a factor or divider, so that the value is small. Meanwhile, the KPK is a multiple, which of course has a large value and looks at the model of the question